2014
DOI: 10.1590/0104-07072014002230013
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of relative caregivers of elderly dependents at home

Abstract: ABSTRACT:The objective of this study was to analyze the relationship of sociodemographic characteristics and activity overload with the quality of life of relative caregivers of elderly dependents at home. This is an epidemiological, transversal study, conducted with 58 relative caregivers of elderly people registered in Family Health Programs in a municipality in the state of Bahia. Sociodemographic data were collected; in addition, the Katz Index of Independence, Zarit Burden Interview, and WHOQOL-bref were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
17

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 14 publications
4
25
0
17
Order By: Relevance
“…It was also observed that the age group of 31 to 50 years was predominant in all degrees of kinship. These findings were similar to those of studies with relative caregivers of elderly dependents and caregivers of people with chronic diseases (17,25) , which also found this age group as the most representative and found that the patient's children were the predominant caregivers, followed by the spouse (15,18,26) .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It was also observed that the age group of 31 to 50 years was predominant in all degrees of kinship. These findings were similar to those of studies with relative caregivers of elderly dependents and caregivers of people with chronic diseases (17,25) , which also found this age group as the most representative and found that the patient's children were the predominant caregivers, followed by the spouse (15,18,26) .…”
Section: Discussionsupporting
confidence: 88%
“…The age variation of the participants is similar to national and international studies (15)(16)(17) . The prevalence of the age group of 31-50 years, followed by those over 60 years, is corroborated by data from other researches (18)(19)(20)(21)(22) and provides an interesting reflection -older adults are strongly represented among caregivers.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Conversely, patients with Cushing’s syndrome, who exhibit exaggerated cortisol secretion, display less NREMS and more awakenings during the night, which can also be corrected by interventions that decrease production of glucocorticoids (GCs) (39, 40). These findings strongly suggest that optimal GC concentrations are essential for normal sleep patterns in humans (41, 42). In rats, a similar phenomenon is also observed, with high levels of corticosterone being especially detrimental to NREMS (43).…”
Section: Hormonal Regulation Of Stress-induced Sleep Reboundmentioning
confidence: 89%
“…El cuidado se comprende como una actitud constante que incluye esfuerzo y dedicación, así como entrega, atención y cariño hacia otro/a (Bedoya-Hernández, 2013; Dos Anjos et al, 2014;Gálvez et al, 2013;Henn et al, 2010;Silva et al, 2013). Desde este enfoque, desprendemos que frecuentemente en los estudios, el cuidado se vincula a la enfermedad y a lo patológico, restringiendo aquellas perspectivas desde las cuales se puede entender el cuidado −las que además no suelen ser explicitadas−.…”
Section: B Comprensión Del Cuidadounclassified